A study on null cartan curve in Minkowski 3-space - Isah, Muhammad Abubakar; Kulahci, Mihriban Alyamac (Walter de Gruyter Gmbh, 2020)
Null cartan curves have been studied by some geometers in both Euclidean and Minkowski spaces, but some special characters of the curves are not considered. In this paper, we study weak AW - (k) type and AW - (k) type null cartan curve in Minkowski 3-space E-1(3). We define helix according to Bishop frame in E-1(3): Furthermore, the necessary and sufficient conditions for the helices in Minkowski 3-space are obtained.
Keywords: Null cartan curve; AW(k)-type curve; helix